THE ROLE OF ISLAMIC BOARDING SCHOOLS IN BUILDING THE CHARACTER OF THE YOUNG GENERATION IN THE MODERN ERA - Jannah, Faridatul; Rizquha, Ach.; Rizal, Mohammad Syifaur; Iqna’a, Faiq Julia Iqna’a Julia (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
Nurul Jadid Islamic Boarding School plays a strategic role in building the character of the young generation in the modern era. This Islamic boarding school applies a holistic educational approach that includes intellectual, emotional, social, and spiritual aspects. The methods used, such as instilling religious values, personal interaction between caregivers and students, and extracurricular activities, have proven effective in forming the character of students who are noble and resilient in facing the challenges of the times. However, Islamic boarding schools also face significant challenges, including the influence of digital culture, the need to adapt to technology, and rapid social change. Nevertheless, Nurul Jadid Islamic Boarding School is able to answer these challenges through curriculum innovation, technology integration in learning, and a balance between tradition and modernity. The relevance of Islamic boarding schools in the digital era is strengthened by their ability to utilize technology as a means of education and provision of global skills. Islamic boarding schools not only maintain the core values of Islam but also provide students with relevant skills and insights to compete in the worldwide world. In conclusion, Nurul Jadid Islamic Boarding School has succeeded in becoming a model educational institution that integrates Islamic traditions with modernity. It remains relevant and contributes significantly to forming a young generation that is religious, intelligent, and ready to face the digital era. This study confirms that Islamic boarding schools can be a solution to building a generation with character amidst the challenges of globalization and technological developments.